Maximizing competitive strategies in the general framework of the critical success factors and the risk management process: applied research in a sample of Iraqi private banks - حمود سعد علي; عمير عراك عبود (Journal of Economics and Administrative Sciences, 2015)
Discussion dealt with the independent factors critical such us success factors and the risk management process, and dependent factor of the general competitive strategies, and began searching the dilemma of thought, as crystallized his problem in the light of the need for organizations to philosophy and deeper vision of a more comprehensive understanding of the concept of risk management, assessment and management to maximize the competitive strategies of public, and on this basis, Search queries formulated problem of the gap between the knowledge-based intellectual propositions farcical for the purposes of interpretation of the relationship between the critical success factors and the risk management process, and likelihood maximize the output of the production process. And manifested aim of the research in determining the extent of benefit from risk management to maximize the output of the production process of the private Iraqi banks, and the diagnosis of the critical success factors for the risk management process, and submit proposals that could contribute to clarifying these modern concepts in the field of strategic thinking, and test the Iraqi environment to incubate Search and rely on the analytical style of the survey, was the use of a linear programming approach to test the hypothesis of the research, data was collected through structured interviews for (48 (a director of the upper and middle departments and operational in twelve private Iraqi banks The research found the impact of the critical success factors and the risk management process to maximize the general competitive strategies, being the output of the production process of the Iraqi private banks. And conclude the existence of the critical success factors for the risk management process, and the existence of interest in the risk management process changes to reduce non-core activities in the banks, and the protection of its resources. The recommended research need to invest critical success factors for risk management and the need for sustaining order to maximize the added value of strategic competitiveness and encourage investment process of risk management, and propose to conduct a study of the impact of strategies to address the risks to strategic performance of the business organizations through the comparison between private banks Iraqi and regional, and create a specialized center for risk management